The spy who loved me? Cross‐partisans in the core executive. (15th March 2018) - Askim, Jostein; Karlsen, Rune; Kolltveit, Kristoffer
Abstract : Political appointees from different parties from that of their minister—cross‐partisan appointees (CPAs)—are increasingly found in the core executive. Ministerial advisory scholarship has overlooked CPAs, while the coalition governance literature sees them as 'spies' and 'coalition watchdogs'. This article argues theoretically and demonstrates empirically that this conceptualization is overly limited. The empirical basis is a large‐N survey of political appointees from two Norwegian coalitions, and a qualitative follow‐up survey of CPAs. The results show that CPAs monitor on behalf of their party, provide cross‐partisan advice to their minister and perform many of the same tasks as regular partisan appointees, including exercising independent decision‐making power. In this research context, most CPAs act as coalition liaison officers who, rather than create tension and negative dynamics, contribute to building trust between coalition partners.